2014
DOI: 10.3389/fpsyg.2014.01268
|View full text |Cite
|
Sign up to set email alerts
|

Thinking before sinning: reasoning processes in hedonic consumption

Abstract: Whereas hedonic consumption is often labeled as impulsive, findings from self-licensing research suggest that people sometimes rely on reasons to justify hedonic consumption. Although the concept of self-licensing assumes the involvement of reasoning processes, this has not been demonstrated explicitly. Two studies investigated whether people indeed rely on reasons to allow themselves a guilty pleasure. Participants were exposed to a food temptation after which passive and active reasoning was assessed by aski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 27 publications
0
19
0
2
Order By: Relevance
“…Taylor, Webb, and Sheeran (2014) found that such conf licts can give rise to justifications for indulgence that can undermine the realization of intentions. Taken together with research on self-licensing (e.g., De Witt Huberts, Evers, & De Ridder, 2012;2014a, 2014b, it seems that there are times when people willingly undermine their own intentions by justifying so doing to themselves.…”
Section: Basis Of the Intentionmentioning
confidence: 96%
“…Taylor, Webb, and Sheeran (2014) found that such conf licts can give rise to justifications for indulgence that can undermine the realization of intentions. Taken together with research on self-licensing (e.g., De Witt Huberts, Evers, & De Ridder, 2012;2014a, 2014b, it seems that there are times when people willingly undermine their own intentions by justifying so doing to themselves.…”
Section: Basis Of the Intentionmentioning
confidence: 96%
“…However, over the last couple of years, it is becoming more acknowledged that self‐regulation failure is not always the result of being unable to inhibit impulses (De Witt Huberts, Evers, & de Ridder, ; Fujita, ; Inzlicht & Schmeichel, ; Gillebaart & de Ridder, ). That is, failure to adhere to long‐term goals can also stem from deciding to (temporarily) abandon one's goal, by relying on reasons to justify this goal disengagement (see De Witt Huberts, Evers, & de Ridder, ). This phenomenon is referred to as self‐licensing: “the act of making excuses for one's discrepant behavior before actual enactment, such that the prospective failure is made acceptable for oneself” (De Witt Huberts et al., , p. 121).…”
Section: Introductionmentioning
confidence: 99%
“…The idea that the 'temptingness' of an option directly affects motivated reasoning finds some support in recent research by De Witt Huberts, Evers, and De Ridder (2014). In their research, female students rated the temptingness of a chocolate bar and indicated which of 30 reasons from a list they would find a good reason to eat the chocolate bar (Study 1) or wrote down the reasons they could think of to eat it (Study 2).…”
Section: Temptation-based Reasoning: When Tempted Everything Becomesmentioning
confidence: 96%